Chemical Constituents and Their Biological Activities from Genus Styrax - Ding-Ding Xia; Xin-Yu Han; Yu Zhang; Na Zhang (MDPI AG, 2023)
Plants from the genus Styrax have been extensively used in folk medicines to treat diseases such as skin diseases and peptic ulcers and as an antiseptic and analgesic. Most Styrax species, especially Styrax tonkinensis, which is used as an expectorant, antiseptic, and analgesic in Chinese traditional medicine, could screen resin after external injury. Styrax is also used in folk medicines in Korea to treat sore throat, bronchitis, cough, expectoration, paralysis, laryngitis, and inflammation. Different parts of various Styrax species can be widely employed for ethnopharmacological applications. Moreover, for ethnopharmacological use, these parts of Styrax species can be applied in combination with other folk medicines. Styrax species consist of versatile natural compounds, with some of them exhibiting particularly excellent pharmacological activities, such as cytotoxic, acetylcholinesterase inhibitory, antioxidant, and antifungal activities. Altogether, these exciting results indicate that a comprehensive review of plants belonging to this genus is essential for helping researchers to continuously conduct an in-depth investigation. In this review, the traditional uses, phytochemistry, corresponding pharmacological activities, and structure-activity relationships of different Styrax species are clarified and critically discussed. More insights into potential opportunities for future research are carefully assessed.